Multi-layer microfluidic glass chips for microanalytical applications - Daridon, Antoine; Fascio, Valia; Lichtenberg, Jan; Wütrich, Rolf; Langen, Hans; Verpoorte, Elisabeth; de Rooij, Nicolaas F. (My University, 2001)
A new, versatile architecture is presented for microfluidic devices made entirely from glass, for use with reagents which would prove highly corrosive for silicon. Chips consist of three layers of glass wafers bonded together by fusion bonding. On the inside wafer faces a network of microfluidic channels is created by photolithography and wet chemical etching. Low dead-volume fluidic connections between the layers are fabricated by spark-assisted etching (SAE), a computer numerical controlled (CNC)-like machining technique new to microfluidic system fabrication. This method is also used to form a vertical, long path-length, optical cuvette through the middle wafer for optical absorbance detection of low-concentration compounds. Advantages of this technique compared with other, more standard, methods are discussed.
When the new glass-based device for flow-injection analysis of ammonia was compared with our first-generation chips based on silicon micromachining, concentration sensitivity was higher, because of the longer path-length of the optical cuvette. The dependence of dispersion on velocity profile and on channel cross-sectional geometry is discussed. The rapid implementation of the devices for an organic synthesis reaction, the Wittig reaction, is also briefly described.